Teach your self web Publishing with HTML 3.0 in a week - Laura Lemay (Samsnet, 1996)
Understanding HyperText and the world wide Web; Simple Web Documents; Doing more; HTML moves Ahead; Multimedia on the web: Images, Sound, and video; Designing Effective documents; Putting it all Online.